2022
DOI: 10.1186/s13048-022-01036-7
|View full text |Cite
|
Sign up to set email alerts
|

Artificial oocyte activation may improve embryo quality in older patients with diminished ovarian reserve undergoing IVF-ICSI cycles

Abstract: Background Artificial oocyte activation (AOA) is used to improve fertilization rate following fertilization failure after intracytoplasmic sperm injection (ICSI). Several studies have also shown that AOA may be involved in embryo development. Women with poor ovarian response are more likely to encounter in vitro fertilization (IVF) failure due to poor embryo quality. The aim of this study was to investigate whether AOA could improve embryo quality in older patients with diminished ovarian reser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
3
2
0
Order By: Relevance
“…Based on our study, we found that AOA treatment can improve the embryo development and reproductive outcome of patients with poor embryo development. This result is consistent with other studies, which demonstrated that AOA treatment can overcome the developmental incompetence of embryos and is an additional indication for ionophore treatment ( 14 , 28 ). It was reported that the different frequencies and patterns of calcium oscillations could affect the induction of oocyte activation and embryo development ( 29 ).…”
Section: Discussionsupporting
confidence: 93%
“…Based on our study, we found that AOA treatment can improve the embryo development and reproductive outcome of patients with poor embryo development. This result is consistent with other studies, which demonstrated that AOA treatment can overcome the developmental incompetence of embryos and is an additional indication for ionophore treatment ( 14 , 28 ). It was reported that the different frequencies and patterns of calcium oscillations could affect the induction of oocyte activation and embryo development ( 29 ).…”
Section: Discussionsupporting
confidence: 93%
“…Based on our study, we found that AOA treatment can improve the embryo development and reproduction outcome of patients with poor embryo development. This result is consistent with another study, which demonstrated that AOA treatment can overcome developmental incompetence of embryos and which is an additional indication for ionophore treatment [11,23]. It was reported the different frequencies and patterns of calcium oscillations could affect the induction of oocyte activation and embryo development [24].…”
Section: Discussionsupporting
confidence: 92%
“…Despite the modest size and limited scope of this group, it can still provide us with some useful information. Additionally, this supports some literature reports on the significance of oocyte activation 16 , 17 . In addition, we observed that patients with IVF low fertilization in the first cycle also resulted in higher live birth rates.…”
Section: Discussionsupporting
confidence: 91%